2013
DOI: 10.1371/journal.pone.0073571
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic Acid Enhances Heat Stress-Impaired Intestinal Epithelial Barrier Function in Caco-2 Cells

Abstract: ObjectiveDysfunction of the intestinal epithelial tight junction (TJ) barrier is known to have an important etiologic role in the pathophysiology of heat stroke. N-3 polyunsaturated fatty acids (PUFAs), including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), play a role in maintaining and protecting the TJ structure and function. This study is aimed at investigating whether n-3 PUFAs could alleviate heat stress-induced dysfunction of intestinal tight junction.MethodsHuman intestinal epithelial Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 48 publications
5
46
0
Order By: Relevance
“…Gut flora, an important index of gastrointestinal health status, was found to be improved in weaned piglets given brown algae (6). Further, omega 3 PUFAs were found to be protective in the intestinal mucosal barrier of tight junction in heat-stressed rats (35). The numerical decrease in DAO in plasma indicates that microalgae supplementation may protect the intestinal mucosa from severe injury under heat stress.…”
Section: Discussionmentioning
confidence: 96%
“…Gut flora, an important index of gastrointestinal health status, was found to be improved in weaned piglets given brown algae (6). Further, omega 3 PUFAs were found to be protective in the intestinal mucosal barrier of tight junction in heat-stressed rats (35). The numerical decrease in DAO in plasma indicates that microalgae supplementation may protect the intestinal mucosa from severe injury under heat stress.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies indicated that the heat-induced increase in paracellular permeability is mainly associated with TJ proteins assembly (Dokladny et al, 2006(Dokladny et al, , 2008. Xiao et al (2013) described that the occludin and ZO-1 mRNA and protein levels were decreased in Caco-2 cells exposed to severe thermalstress for 1 h (43°C) and n-3 polyunsaturated fatty acids protected this heat-induced permeability dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…Heat-induced multi-organ injury may include varying degrees of central nervous system dysfunction, acute renal failure, liver failure, skeletal muscle injury and gut ischaemia (Leon & Helwig, 2010). An important early symptom of thermal stress is a dysfunction of the intestinal barrier leading to increased intestinal permeability and as a consequence increased entrance of toxic luminal substances (Dokladny, Moseley, & Ma, 2006;Xiao et al, 2013). With the prospect of increasing global warming and increase in frequency and intensity of heat stress (Bouchama & Knochel, 2002), it is important to investigate preventive measures that can alleviate adverse effects of exposure to high environmental temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Long-chain n −3 PUFA might also contribute to mitigate intestinal MeHg absorption (Xiao et al, 2013). Analytical and in vitro studies are on-going to elucidate the different chemical forms and bioavailability of Se and Hg in Nunavik country foods, as well as the influence of country food nutrients on Hg intestinal absorption.…”
Section: All (N = 702)mentioning
confidence: 99%